Theism in the Language of Humanism: Reincarnations of the Transcendent God in the Secular Subject (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The process of secularization can be defined as a shift in the focus of European thought from the transcendent God, the otherworldly, and the suprahuman, towards immanence, that is, towards the world and the human condition in the world. Secularization represents a transition from theism to humanism. Given this definition, it is often concluded that secularization has led to the exclusion of God from thought and the removal of religion from society. Nevertheless, post-secular thought offers a more nuanced and sophisticated perspective. As postulated by numerous theorists, secularization was not a departure from theism and religion in general, but rather a departure from a specific conception of God and a particular mode of religiosity that had been dominant for an extended period. Most contributions to this volume identify the moments of secularization and humanism, not as the elimination of God but on the contrary as an opportunity that various thinkers recognized to liberate the divine from the constraints of hegemonic European theology and religiosity. This perspective suggests that secularization did not erase God but rather created an opportunity for the humanization of religion through ethical, social, or political activation. The papers in this volume take different approaches and offer different responses to the question of how the divine and the transcendent reappear in the discourse of humanism.